Assessment of acid attack on concrete containing spent garnet as partial sand replacement - Budiea, Ahmed Mokhtar Albshir; Yee, Hau Chong; Shahrul Niza, Mokhatar; Khairunisa, Muthusamy; Mohamed Abdel Kader, IsmaiI (Sustainable Building Research Center (ERC) Innovative Durable Building and Infrastructure Research Center, 2022)
Excessive sand mining for concrete production and disposal spent garnet waste from industrial activity causes environmental degradation. These degraded materials need to be inclined with other ways such as being a substitution of fine aggregate thus, preserving the environmental resources. The purpose of this study is to investigate the durability aspect of concrete containing spent garnet in acidic environment. Spent garnet was used as partial sand replacement with 0%, 10%, 20%, 30% and 40% in each of the concrete mixes designed respectively. Initially, the water absorption test was conducted on sets of 3 water-cured concrete cubes for the plain concrete and also for each percentage of spent garnet concrete mixes. Furthermore, the durability tests under 5% of hydrochloric acid and 5% of sulphuric acid solutions were conducted. Sets of concrete specimens which were 3 set of 28 days water-curing specimens for each percentage of spent garnet in each type of acid immersion have been evaluated respectively. Additionally, another set of concrete specimens containing 3 cubes for each spent garnet content was cured in water for 56 days for the comparison purposes. At the end of the study, the highest percentage of water absorption was concrete mix of 20% sand replaced with spent garnet (C20). Other than that, the stronger average concrete strength of concretes from both acids with the achieved target compressive strength was concrete C20 which having 30.8MPa and 19.3MPa for each acid, respectively. The concrete containing 20% of spent garnet had better acid resistant in terms of visual assessment not only towards sulphuric acid attack but also towards hydrochloric acid attack. Conclusively, the utilization of spent garnet in concrete mixture could bring good expectation as partial sand replacement for construction industry resulting of conserving the natural resources.